The Effectiveness of an ICT-Based Problem-Based Learning Model on Students’ Mathematical Literacy Skills and Learning Interest - Nada, Adiba I’lliyyun; Lestari, Mulyaningrum; II2, Salvador V. Briones (Universitas Islam Negeri Sunan Kudus, 2025)
In the Industrial Revolution 4.0 era, education faces challenges such as low mathematical literacy and limited student interest. One solution is implementing a Problem-Based Learning (PBL) model supported by Information and Communication Technology (ICT)-based media. This study used Microsoft PowerPoint for visual presentations, YouTube videos, and worksheets for practice problems. These tools were selected for their relevance to mathematics content, accessibility, and alignment with PBL steps to enhance engagement. Learning materials were teacher-developed and contextualized with statistics topics. This study aimed to: (1) determine the effectiveness of the ICT-based PBL model in improving mathematical literacy compared to direct learning, and (2) examine its effect on students’ learning interest. A quantitative quasi-experimental method with a posttest-only control group design was used, involving 64 junior high school students (32 experimental, 32 control). Data were collected through validated instruments: a mathematical literacy test (reliability 0.87) and a learning interest questionnaire (reliability 0.82). Data analysis using an independent sample t-test confirmed significant differences (p < 0.05). The experimental group achieved higher mean scores in mathematical literacy (82.56) and learning interest (84.33) than the control group (74.18 and 76.41). The t-values (3.42 and 3.09) exceeded the critical value (t₀.₀₅ = 2.00). These findings indicate that the ICT-based PBL model effectively improves mathematical literacy and learning interest. Practically, mathematics teachers are encouraged to integrate ICT-based PBL into instruction, supported by adequate ICT facilities and teacher training. Di era Revolusi Industri 4.0, dunia pendidikan menghadapi tantangan berupa rendahnya kemampuan literasi matematis dan kurangnya minat belajar siswa. Salah satu solusi yang dapat diterapkan adalah penggunaan model Problem-Based Learning (PBL) yang didukung media berbasis Teknologi Informasi dan Komunikasi (TIK). Media TIK yang digunakan dalam penelitian ini meliputi Microsoft PowerPoint untuk presentasi visual, video pembelajaran dari YouTube, serta lembar kerja siswa. Media tersebut dipilih berdasarkan relevansinya dengan materi matematika, kemudahan akses, dan kesesuaiannya dengan langkah-langkah PBL untuk meningkatkan keterlibatan siswa. Seluruh bahan ajar dikembangkan oleh guru dan dikontekstualisasikan dengan materi statistika. Penelitian ini bertujuan untuk: (1) mengetahui efektivitas model PBL berbasis TIK dalam meningkatkan literasi matematis dibandingkan pembelajaran langsung, dan (2) menelaah pengaruhnya terhadap minat belajar siswa. Metode yang digunakan adalah kuantitatif dengan desain eksperimen semu posttest-only control group. Sampel penelitian terdiri atas 64 siswa SMP negeri (32 kelompok eksperimen dan 32 kelompok kontrol). Data dikumpulkan melalui tes literasi matematis (reliabilitas 0,87) dan angket minat belajar (reliabilitas 0,82). Hasil analisis menggunakan independent sample t-test menunjukkan perbedaan signifikan (p < 0,05). Rata-rata literasi matematis kelompok eksperimen (82,56) dan minat belajar (84,33) lebih tinggi dibandingkan kelompok kontrol (74,18 dan 76,41). Dengan demikian, model PBL berbasis TIK terbukti efektif meningkatkan literasi matematis dan minat belajar siswa, serta direkomendasikan untuk diterapkan oleh guru dengan dukungan fasilitas dan pelatihan TIK yang memadai.